Penerapan Etika Bisnis Islam Dalam Pemasaran Produk UMKM Untuk Meningkatkan Kepercayaan Dan Loyalitas Konsumen - Chasanah, Siti (CV. ULIL ALBAB CORP, 2025)
A crucial component of creating a company plan that respects Islamic principles while also being profitable is halal marketing ethics. The implementation of halal marketing ethical standards may help Muslim MSMEs establish consumer trust and loyalty, particularly as public knowledge of halal goods grows. This research seeks to investigate the application of halal marketing ethics in Muslim MSME commercial operations and its effects on customer attitudes. This study uses a qualitative-descriptive methodology to examine ethical aspects of marketing operations like honesty, transparency, fairness, and social responsibility. The findings of the study demonstrate that halal ethics-based strategies not only improve long-term customer connections, but also serve as a significant differentiator in a competitive marketplace. As a result, the emphasis in the sustainable development of Muslim MSME enterprises should be on incorporating ethical values into marketing.